COMPARISON BETWEEN LIGASURE HEMORRHOIDECTOMY AND MILLIGAN MORGAN HEMORRHOIDECTOMY IN TERMS OF OPERATIVE TIME, POST-OPERATIVE PAIN AND BLEEDING - HASSAN, G; SABIR, M; YASEEN, G; ALI , M; FAREED, N; BHATTI, A (Biological and Clinical Sciences Research Journal, 2024)
The gold standard treatment for symptomatic stage III and IV hemorrhoidal disease is hemorrhoidectomy, which is a surgical procedure. To improve outcomes and minimise complications, ligasure hemorrhoidectomy is one of the new techniques being used. Objective: The objective of this study was to compare Ligasure Hemorrhoidectomy and Milligan Morganm Haemorrhoidectomy in terms of operative time, postoperative pain and bleeding. Methods: The study was conducted at the Department of General Surgery in DG Khan Medical College DG Khan from 1st September 2023 to 31st August 2024 after obtaining permission from the ethical board of the institute. 64 participants of both genders and different age groups were enrolled in this study. Individuals whose ages were 18 to 80 years who had 3rd-stage haemorrhoids and were able to tolerate spinal anaesthesia were included. Participants were randomly divided into two equal groups. Group A is undergoing Ligasure hemorrhoidectomy and Group B is undergoing Milligan Morgan hemorrhoidectomy. A specifically created proforma with bio-data and relevant particulars was used to gather data on blood loss, operating time and pain. SPSS V-24 was used for the data analysis. The independent sample t-test was used to compare blood loss operative time and pain severity. A P-value of less than 0.05 was considered significant. Results: A total of 64 individuals participated in this study out of which males were 43(67.18%) and females were 21(32.8%). The age ranged from 18-80 years and the mean age in group A participants was 51.40 ± 14.90 years while in group B it was 49.47 ± 13.63 years. In group A (Ligasure ) the mean post-operative pain score was 5.39 ± 2.51 while in group B (Milligan Morgan) was 8.53 ± 3.78 (the P value equal to 0.0001). In group A (Ligasure), the mean blood loss during surgery was 2.47 ± 1.22 ml, but in group B the operation), it was 18.83 ± 4.44 ml (where p 0.0001). Group A mean operation time was 32.8 ± 6.78 minutes, whereas group B was 39.69 ± 5.89 minutes. Conclusion: Ligasure haemorrhoidectomy is time-sparing and associated with less post-operative pain and post-operative bleeding as compared to conventional Milligan Morgan hemorrhoidectomy.